Impact of a movie club on the well-being of Buckinghamshire psychiatry doctors facing moderate-to-high burnout risk - Sureyya Melike Toparlak (BJPsych International)
Burnout is a common issue among healthcare professionals and can have a negative impact on both personal and professional well-being. This initiative follows a group of doctors working in Buckinghamshire, UK, who are at moderate to high risk of burnout, over 6 months to determine whether participation in a movie club, as a form of stress relief and social support, can have a positive impact on well-being. The aim of the project was to investigate the impact on doctors’ well-being by improving connectedness, reducing the feeling of isolation and encouraging face-to-face activities.